Biomedical Applications of Metal−Organic Frameworks for Disease Diagnosis and Drug Delivery: A Review - Al Sharabati, Miral Osama Yacoub (2021)
Metal−organic frameworks (MOFs) are a novel class of porous hybrid organic−inorganic materials that have attracted increasing attention over the past decade. MOFs can be used in chemical engineering, materials science, and chemistry applications. Recently, these structures have been thoroughly studied as promising platforms for biomedical applications. Due to their unique physical and chemical properties, they are regarded as promising candidates for disease diagnosis and drug delivery. Their well-defined structure, high porosity, tunable frameworks, wide range of pore shapes, ultrahigh surface area, relatively low toxicity, and easy chemical functionalization have made them the focus of extensive research. This review highlights the up-to-date progress of MOFs as potential platforms for disease diagnosis and drug delivery for a wide range of diseases such as cancer, diabetes, neurological disorders, and ocular diseases. A brief description of the synthesis methods of MOFs is first presented. Various examples of MOF-based sensors and DDSs are introduced for the different diseases. Finally, the challenges and perspectives are discussed to provide context for the future development of MOFs as efficient platforms for disease diagnosis and drug delivery systems.